Hypothalamic hamartoma with gelastic seizures: a case report - ., Zosangliani; Datta, Avishek; Thele, Rukuwe; Gurung, Bishal; Kambiakdik, T. (International Journal of Contemporary Pediatrics, 2020)
Hypothalamic Hamartoma (HH) may have diverse clinical manifestations. Its hallmark association is with gelastic seizures. Gelastic epilepsy is characterized by episodes of loud, hollow, mirthless, stereo-typed, forced laughter. The patient may stare and giggle briefly without any other motor manifestations. Hypothalamic hamartoma is most often the cause of gelastic seizures. Here, authors report a case of gelastic seizure with hypothalamic hamartoma in a 14-month-old boy with an associated tonic clonic seizure. This case highlights the possibility of underdiagnosed hypothalamic hamartoma in younger age groups among pediatric population.